Developing second order cybernetics - Scott, Bernard (Kybernetes, 2004)
Special double issue: developing second order cybernetics - a collection of papers from the UK Cybernetics Society Guest Editor: Bernard Scott This special double issue is based on the presentations made at a conference with the theme "Second Order Cybernetics (SOC)", which had been organised by the UK Cybernetics Society in London in 2002. Previously published in: International Journal of Systems & Cybernetics, Volume 33, Number 9/10, 2004